Efektivitas Food Product Dalam Memenuhi Kebutuhan Tamu di Hotel Gran Puri Manado - Aneke W; Sonny Wijanarko; Agus Walansendouw (Jurnal Hospitaliti, 2022)
The Food Product activity in Food and Beverage Department, depend on the preparing Food and Beverage for selling to guest with service good to satisfaction guest the following procedures. In business world today, the service quality as Human Resources is the most important, thing in developing the company in service. Hotel is Hospitality Industry, especially in serving the guest satisfied good service must be supported by good service provider related with the every employee at company. To analyze data, the writer uses description qualitative method. The result of this research shows that Food and Beverage Preparing to Food Product Following Procedures is done by Food and Beverage Product Department in Hotel Gran Puri Manado.